Toolbox Redesign for Flight Engineer - Beti Rahmadani; Moch Junaidi Hidayat (Journal of Industrial Product Design Research and Studies, 2022)
Toolbox is a tool rack made with the aim that service tools are arranged according to the tools that are often used by technicians and the tools are safer when not in use by Flight Engineers. Flight Engineer is part of aviation safety which is closely related to the physical plane and aspects of maintenance so that Flight Engineering requirements are met. When carrying out their work, Flight Engineers need a container or facility as a place to put Flight Engineer equipment that can contain a lot of work equipment, is efficient, easy to carry and move. The toolbox redesign process is carried out to make changes and add functions from the existing toolbox design and use at that time. This study uses a mixed method with qualitative and quantitative approaches. Qualitative data obtained from interviews and photo documentation obtained from Flight Engineer sources. Quantitative data obtained by observing the measurement of toolbox dimensions at the Juanda Navy Aviation Center and Biak Air Base. The design concept applied to the design of the equipment box is functional. The results of this research are work equipment icon designs, equipment placement layouts in the toolbox, 10 initial toolbox design sketch designs, five alternative toolbox designs, and one selected toolbox design. The two selected toolbox designs will be developed into a final product design.